Antioxidant activity on protein hydrolysate peptide of mudskipper fish (Periophthalmodon schlosseri) using alcalase enzyme - KARNILA, Rahman; DEWITA, Edison; YOSWATY, Dessy; YOSWATY, Dessy; PUTRI, Triatma; YUNUS, Anastasia (Food Science and Technology, 2023)
Mudskipper fish is an endemic amphibian fish that has high potential to be developed into fish protein hydrolysate due to the high protein content (92% per dry weight). The aim of the research was to obtain new peptide compounds and hydrolyze the antioxidant activity of mudskipper fish (Periophthalmodon schlosseri). The design used in this study was a completely randomized design (CRD) with enzyme concentrations of 1.5 and 2% with three repetitions. The data obtained were analyzed using descriptive statistics and ANOVA. The results showed that mudskipper fish has the proximate content in the form of water content of 79.13% (wb), protein of 91.85% (db), fat of 1.50% (db), and ash of 4.54% (db), with glutamate amino acid being the highest (6.78%). The protein content of large molecular weight in fish protein hydrolysate obtained using an enzyme concentration of 1, 1.5, and 2% is relatively small, namely, 24.62, 4.85, and 9.47%, respectively. Several peptide compounds were identified in the hydrolysate using enzyme concentrations of 1, 1.5, and 2%, respectively: L-Arg-L-Pro, Phe-Pro, and L-Leu-L-Leu-L-Glu; L-Leu-L-Pro, L-Arg-L-Pro, and L-Leu-L-lys-L-Pro; and lys-Leu, L-Leu-L-Pro, Leu-Trp-Gln-Thr, L-Tyr-L-Gln-L-Val-L-Pro, L-Tyr-L-Gln-L-Leu-L-Pro, and L-Leu-L-Ser-L-Phe-L-Ala-L-α-Gln-L-Pro-Gly. Furthermore, the hydrolysate obtained effectively scavenged DPPH free radicals with IC50 values of 10.98±0.57%v/v, 4.04±0.79%v/v, and 8.69±0.028%v/v, respectively.